QTC Prolongation in Patients of Haemorrhagic Stroke - Hira Anum, Mehroze Sajjad, Aftab Hussain Turi, Burhan Ahmad, Saima Tabassum, Shumaila Maqsood, Usama Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:To evaluatethe frequency of QTC Prolongation among the patients of haemorrhagic stroke Methodology: A total of 120 cases of hemorrhagic stroke between 20-70 years of age of either gender presenting first time were enrolled from Rehmat-u-lil Alameen Institute of Cardiology, Lahore during the year May,2021 to April 2022. QT interval is a good non-invasive diagnostic indicator of ventricular repolarization and myocardial homogeneity. Low Glasgow coma scale (GCS), brain stem involvement, and a prolonged QTc interval are all poor prognostic indicators of hemorrhagic stroke. Results:In our study, 20-50 years aged patients were recorded in 31.67%(n=38) and 68.33%(n=82) were between 51-70 years of age. Male gender were 61.67%(n=74) and 38.3%(n=46) were females.QTC prolongation was recorded in 34.17%(n=41) whereas 65.83%(n=79) had no QTC prolongation. Conclusion: It is concluded by the results that frequency of QTc prolongation was higher in hemorrhagic strokecases, however, it is required that every stroke patient should be evaluated for cardiac examination so that early detection may reduce cardiac morbidities